The challenges and constructive role of journalism during covid-19 in communication ecology of pandemic reporting in the global south - Khan, Sanan Waheed; Abdullah, Zulhamri; Raza, Syed Hassan; Siriphan, Thathira; Mookda, Rarina; Fitriani, Rani Siti (IGI Global, 2023)
The COVID-19 pandemic has presented various challenges for journalism and the media in the Global South. In many countries, media outlets are struggling to cover the pandemic due to limited resources, weak infrastructure, and the impact of government restrictions on freedom of expression. During the COVID-19 outbreak, the media must acquire and distribute correct information. This research examines the discursive creation of journalism during the COVID-19 conflict. The researcher analyzed discourses on the coronavirus pandemic from interviews with journalists and the Pakistani journalism trade press. In COVID-19, journalists discursively positioned themselves as responsible yet susceptible members of the communication ecology, not just because of the pandemic but also environmental factors that preceded it. The study concludes that health reporters in Pakistan can filter fake news during the COVID-19 pandemic by verifying information, fact-checking, using trusted sources, avoiding sensationalism, and collaborating with medical experts.